Designing facilitated task constraints for different age groups in soccer: The impact of floaters` rules - Praça, G. M.; Moreira, P. E. D.; Rochael, M.; Barbosa, G.; Travassos, B. (International Journal of Sports Science & Coaching, 2022)
This study compared the influence of changing floaters? rules on player positioning in small-sided games (SSG) played by different age groups. A total of 48 youth soccer players (24 U-13 and 24 U-14) took part in the study, playing three different SSGs: regular 3vs3, 1-floater condition (one floater playing for both teams), and 2-floater condition (one floater per team, with alternate participation). Positional data were collected by 5 Hz GPS devices, generating individual (spatial exploration index) and collective (teams length, width, length per width ratio, and stretching index) positional variables. The results revealed that the 2-floater format significantly reduced the length (p=0.001), and both formats with floaters increased the width (p<0.001). Also, the 1-floater format presented the lowest stretching index (p<0.001). Concerning age-group differences, older players presented higher values of length (p<0.001), length per width ratio (p<0.001), and spatial exploration index (p<0.001) than their younger counterparts. The 2-floater SSG format is a more facilitated and simplified version of numerically unbalanced SSGs, which might be considered by coaches when designing tasks adjusted to the level of the athletes.